Measurement of Successful Implementation of Institution Level Financial Application System (SAKTI) Web Full Module with DeLone and McLean Information System Success Model Approach - R. Muhammad Rizqi At-tamimi; Tety Elida Siregar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Directorate General of Treasury (DJPB), Ministry of Finance, has developed a system that is integrated with all work units (Satker) of central government agencies throughout Indonesia, named the Institutional Level Financial Application System (SAKTI). The purpose of this study is to measure how successful the implementation of the SAKTI web full module which is in the phase II trial phase at the Ministry of State Secretariat is, as well as to analyze the factors that influence the success of using the DeLone and McLean (2003) Information System Success Model approach. The sample selection method used is a non-probability method using purposive sampling technique and getting as many as 98 respondents in this study. The results of the analysis using Partial Least Square- Structural Equation Modeling (PLS-SEM), show that system quality and information quality have a significant positive effect on user satisfaction, while in this study service quality has no effect on SAKTI web user satisfaction. This study also provides empirical evidence that user satisfaction has a positive and significant effect on the SAKTI web in terms of user perceptions of the system's ability to contribute which has an impact on improving its performance. The results of the Fit Model test in this study showed a good fit based on the SRMR value of 0.065. Meanwhile, based on the NFI value, it can be concluded that the fit of the model in this study is 74%.